1998
DOI: 10.1161/01.cir.98.21.2235
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Coronary Effects of the Endothelin Antagonist Bosentan in Patients With Coronary Artery Disease

Abstract: Background-Endothelin is a potent endothelium-derived vasoconstrictor peptide with proliferative properties. Elevated levels of the peptide occur in coronary artery disease; however, its pathophysiological role as a regulator of coronary tone and structure is uncertain. Endothelin-receptor antagonists are specific tools to clarify this issue and might be useful in the treatment of coronary artery disease. Methods and Results-In a double-blind, placebo-controlled randomized study, we investigated the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 38 publications
(34 reference statements)
2
53
1
1
Order By: Relevance
“…Indeed, it has recently been shown that endogenous ET-1 exerts a vasoconstrictor effect in the epicardial arteries of patients with coronary artery disease, as evidenced by the vasodilation through the ET-1 receptor antagonist bosentan. 20 Interestingly, in media subjacent to a CP, the number of ET-1 ϩ VSMCs is significantly lower than in media beneath a fatty streak lesion, and there is no significant difference between the number of ET-1 ϩ cells in media adjacent to AIF and media subjacent to a CP. This may be due to the medial atrophy with a reduction of the number of VSMCs, which is a common finding subjacent to advanced atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, it has recently been shown that endogenous ET-1 exerts a vasoconstrictor effect in the epicardial arteries of patients with coronary artery disease, as evidenced by the vasodilation through the ET-1 receptor antagonist bosentan. 20 Interestingly, in media subjacent to a CP, the number of ET-1 ϩ VSMCs is significantly lower than in media beneath a fatty streak lesion, and there is no significant difference between the number of ET-1 ϩ cells in media adjacent to AIF and media subjacent to a CP. This may be due to the medial atrophy with a reduction of the number of VSMCs, which is a common finding subjacent to advanced atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 88%
“…Intravenous administration of bosentan to patients with angiographic stable coronary artery disease produced an increase in coronary diameter in those vessels with minimal angiographic changes. 60 The selective ET A receptor blocker BQ-123 given to patients with stable angina was shown to prevent distal coronary vasoconstriction after percutaneous transluminal coronary angioplasty. 61 …”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…In contrast, combined ET AϩB receptor blockade results in both epicardial and microvascular coronary vasodilatation. 31 Thus, endogenous ET-1 has a role in the maintenance of resting coronary vasomotor tone. This reflects a net balance of ET A receptormediated vasoconstriction and ET B receptor-mediated vasodilatation, the latter acting exclusively in resistance vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Differing effects of ET B receptor activation are observed in health and disease and in different vascular beds. 10,16 -19,28 -30 Combined ET AϩB antagonism causes coronary vasodilation, 31 but the effects on endothelial function and the specific role of ET B in coronary vasomotion remain unknown.…”
mentioning
confidence: 99%